Lupe Wong won't dance - Higuera, Donna Barba (Levine Querido, 2020)
"Lupe Wong is going to be the first female pitcher in the Major Leagues. She's also championed causes her whole young life. Some worthy ... like expanding the options for race on school tests beyond just a few bubbles. And some not so much...like complaining to the BBC about the length between Doctor Who seasons. Lupe needs an A in all her classes in order to meet her favorite pitcher, Fu Li Hernandez, who's Chinacan/Mexinese just like her. So when the horror that is square dancing rears its head in gym? Obviously she's not gonna let that slide."--Provided by publisher.